Synthesis, Activity Test and Molecular Docking of Novel Nitrophenylcalix[4]-2-methylresorcinarene Derivatives as Antimalarial Agent - Nisa, Siti Astika; Jumina, Jumina; Mardjan, Muhammad Idham Darussalam; Kurniawan, Yehezkiel Steven (Molekul, 2023)
This research involved the synthesis, antimalarial assay and molecular docking of novel nitrophenylcalix[4]-2-methylresorcinarene derivatives. Calix[4]-2-methylresorcinarene derivatives, i.e., 2N, 3N and 4N, were synthesized in a one-step reaction through the cyclo-condensation reaction between resorcinol and aldehydes, i.e., 2-nitrobenzaldehyde, 3-nitrobenzaldehyde and 4-nitrobenzaldehyde, respectively. The reaction was carried out through the reflux method with ethanol and hydrochloric acid 37% as the solvent and catalyst, respectively. The synthetic products were characterized using FTIR, 1H-NMR, 13C-NMR, and LC-MS spectrometers. Furthermore, the in vitro antimalarial assay was carried out against Plasmodium falciparum strain 3D7. The results showed that the 2N, 3N and 4N compounds were successfully synthesized in 86.4, 78.6 dan 95.7% yield, respectively. The antimalarial activity test of 2N, 3N and 4N gave IC50 values of 2.35, 1.68 and 1.79 µM, therefore, these compounds are classified as active antimalarial agents. Molecular docking performed against the PfLDH receptor showed that the 2N, 3N and 4N compounds had negative binding affinity values of -5.1, -6.1, and -6.0 kcal/mol and had specific interactions in the form of hydrogen bonds to the amino acid residues Arg109, Thr101 and Lys102 in the active site of the receptor. The molecular docking results agreed with the experimental antimalarial assay demonstrating the mechanism of action of nitrophenylcalix[4]-2-methylresorcinarenes as active antimalarial agents happened through the inhibition of the PfLDH receptor.